Burundi’s Withdrawal From The International Criminal Court (ICC) During The Era Of Pierre Nkurunziza’s Government - Fazriyah, Laila Choirul; Susilowati, Ida (Mediasi Journal of International Relations, 2024)
Pierre Nkurunziza's candidacy for a third term as president of Burundi has triggered an increase in crimes against humanity in Burundi and prompted the International Criminal Court (ICC) to open an investigation. In 2016, under Nkurunziza's leadership, Burundi withdrew from the International Criminal Court (ICC). Using an explanatory qualitative research design, this research discusses the factors behind Burundi's decision to withdraw from the International Criminal Court (ICC) during the Nkurunziza administration. Data was collected through literature studies from various books, journals, and national and international official websites. The analysis used the rational actor model approach and classical realism theory to explain Nkurunziza's policy regarding Burundi's withdrawal from the International Criminal Court (ICC). The analysis shows that Nkurunziza's decision to withdraw Burundi from the International Criminal Court (ICC) is based on cost-benefit considerations. Costs obtained by Burundi include loss of attachment to the Rome Statute, a reduction in Burundi's international reputation, and an impact on Burundi's diplomatic relations. While the benefits received by Burundi; Pierre Nkurunziza / state officials are free from International Criminal Court (ICC) investigations into humanitarian violations, have domestic legal control, reduce internal political tensions, and allow the state to apply policy flexibility. This shows that the correlation between state leaders and a country's policies is interrelated.